Thickening of Rubber Sap (Hevea brasilliensis) Through the Utilization of Natural Ingredients Noni Fruit Extract (Morinda citrifolia L.) (Students Field Practice of Human and Environmental Subject) - Muhammad Yassir (Jurnal Serambi Ilmu, 2021)
The purpose of this study was to increase students' knowledge about the benefitsof noni fruit extract (Morinda citrifolia L.) for thickening of rubber latex (Heveabrasilliensis). This research was conducted in 2020 in the village of TerutungPedi, Babussalam District, Southeast Aceh Regency, The method used in thisresearch is the experimental method with a non-factorial Randomized BlockDesign (RAK) designed in five treatments and three replications. The tools is themineral water bottle, blender, notebook, camera, plastic bucket, measuring cup, measuring pipette, knife, filter, stopwatch/Hp and scale. The ingredients is nonifruit (Morinda citrifolia) which is ripe with the characteristics of a white skin andfruit flesh that contains a lot of water and rubber latex (Hevea brasilliensis) thathas been tapped. The conclusion was that the administration of noni fruit extract(Morinda citrifolia L.) had a significant effect on the thickening of rubber latex(Hevea brasilliensis).